Investment Strategy Based on Bias Behavior and Investor Sentiment in Emerging Markets - Dian Safitri Pantja Koesoemasari; Tulus Haryono; Irwan Trinugroho; Doddy Setiawan (ETIKONOMI, 2022)
This research's main objective is to select profitable investment strategies with the presence of sentiment investors in emerging markets, with behavior bias-based portfolio methods. The sample of 114 companies traded daily on IDX was conducted over three years with weekly data. This study uses pairwise comparison and OLS. The research results show that contrarian strategies are more profitable than momentum. Investors benefit when mild conditions are optimistic and more significant when the conditions are pessimistic. This research proves that investor sentiment in the market can distort investor investment decisions, even using the behavior-bias method. Therefore, forming a portfolio will be more appropriate based on biased behavior because it facilitates investment decision-making.How to Cite:Koesoemasari, D.S.P., Haryono, T., Trinugroho, I., Setiawan, D. (2022). Investment Strategy Based on Bias and Investor Sentiment in Ememerging Market. Etikonomi, 21(1), 1-10. https://doi.org/10.15408/etk.v21i1.22290.